Experimental Identification and Control of Solars Dryers for Wood (INGE@UAN - TENDENCIAS EN LA INGENIERÍA, 2015)
This paper presents results of designing and implementation of experiments for modeling two prototypes of solar dryers: with solar thermal contribution and wood energy storage in water. In both cases, the mathematical model was obtained using experimental identification through Output Error. The best model is used for the controller Proportional Integral design in order to control the relative humidity in the drying chamber of a solar dryer for wood energy storage in water. Finally, the simulation and practical implementation of the dryer controlled are presented.
Keywords: Solar Dryers; Solar Energy; Identification; Control System